2019
DOI: 10.3389/fendo.2019.00580
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Presentation but Not in Outcome for ACTH-Dependent Cushing's Syndrome

Abstract: Background: Sex differences in clinical picture of ACTH-dependent Cushing's syndrome are controversial, except for the known higher prevalence in females. We compared a broad range of potential differences to enable a more accurate understanding of the clinical picture of sex-specific ACTH-dependent Cushing's syndrome. Methods: Cohort study including consecutive patients with ACTH-dependent Cushing's syndrome from Leiden and Berlin diagnosed between 2000 and 2016. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
3
11
1
Order By: Relevance
“…Interestingly, we found that male sex was associated with lower BMD in CS patients and men more often had vertebral fractures than women. This is in accordance with several other studies that have shown a higher prevalence of osteoporosis in men than in women with CS (10,31,32,33,34). In our study, men were more often hypogonadal compared with women.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, we found that male sex was associated with lower BMD in CS patients and men more often had vertebral fractures than women. This is in accordance with several other studies that have shown a higher prevalence of osteoporosis in men than in women with CS (10,31,32,33,34). In our study, men were more often hypogonadal compared with women.…”
Section: Discussionsupporting
confidence: 93%
“…Etiology of CS and gender have been suggested to influence BMD and fracture risk in patients with CS (6,7,9,10,11,12,27,28,30,31,32,33,34). Several studies have shown an association between male sex and lower BMD at diagnosis (10,31,32,33,34). Results on the association between etiology of CS and BMD are conflicting.…”
Section: Persistent Improvement Of Bone Mineral Density Up To 20 Year...mentioning
confidence: 99%
“…CSC is a relatively rare disease, for which an incidence of 9.9 per 100,000 for males and 1.7 per 100,000 for females has been described in a retrospective cohort study 30 . Of note, our study included 4 male CS patients and 7 female CS patients and we observed CSC(like) abnormalities in 2 males and 1 female, despite the fact that CS occurs 5 times more often in females 29 . The incidence of CSC(-like) ophthalmological changes, which occurred in 3 out of the 11 CS patients in our study, may suggest that (subclinical) CSC is more likely to occur in CS patients compared to the general population.…”
Section: Discussionmentioning
confidence: 70%
“…Notwithstanding, although there is a common trunk of hypercortisolism in CS, it is very interesting to better understand the origin of CS on CSC by studying a larger cohort -probably multicenter. This would also allow for a more comprehensive analysis of risk factors associated with CSC such as gender, or manifestations of CS such as neuropsychiatric symptoms or biochemical (hormonal) abnormalities such as ACTH 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study between 2000 and 2019 included 130 subjects with ectopic Cushing syndrome (female/male ratio of 93/37) and it showed that the prevalence of osteoporosis was 25 vs. 48% (females vs. males), while the prevalence of vertebral fractures was 5 vs. 16%, suggesting the fact that actually males are more affected than women when it comes to bone status (92). Moreover, the fracture risk was dependent to some extend on low BMD according to central DXA and/or decreased values of TBS; but the main contributor to fracture risk was found to be the level of hypercortisolemia and the time of exposure, not necessary the pathogenic type of Cushing syndrome or the source of ectopic ACTH over-secretion (meaning that it seemed less important that there was an underling NEN in association with ectopic ACTH production in terms of glucocorticoid osteoporosis) (93).…”
Section: Nen-associated Ectopic Cushing Syndromementioning
confidence: 99%